Radiopacity evaluation of root-end filling materials by digitization of images - Tanomaru-Filho, Mario [UNESP]; da Silva, Guilherme Ferreira; Hungaro Duarte, Marco Antonio; Gonçalves, Marcelo [UNESP]; Guerreiro Tanomaru, Juliane Maria [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2008)
The purpose of this study was to evaluate the radiopacity of 5 root-end filling materials (white MTA-Angelus, grey MTA-Angelus, IRM, Super EBA and Sealer 26). Five specimens (10 mm diameter X 1 mm thickness) were made from each material and radiographed next to an aluminum stepwedge varying in thickness from 2 to 16 mm. Radiographs were digitized and the radiopacity of the materials was compared to that of the aluminum stepwedge using VIXWIN 2000 software in millimeters of aluminum ( mm Al). Data were analyzed statistically by ANOVA and Tukey's test at 5% significance level. Radiopacity values varied from 3 mm Al to 5.9 mm Al. Sealer 26 and IRM presented the highest radiopacity values (p<0.05), while white/grey MTA and Super EBA presented the lowest radiopacity values (p<0.05). The tested root- end filling materials presented different radiopacities, white/grey MTA and Super EBA being the least radiopaque materials.
Keywords: Radiopacity; Retrograde obturation; Root canal filling materials; Radiology